Local political movements on the electoral scenario - Lacuisse, Marie-Esther (2007)
This article analyzes the participation of local political movements in the electoral process in Ecuador. Unlike other countries such as Peru, wherein local and regional political movements have been inserted into political life since the eighties, gaining a strong level of representation from the nineties onwards, in Ecuador they stepped onto political stage in 2000, four years after the electoral system had been opened up to political and independent movements. While its representation remains geographically uneven and unstable for partly institutional reasons, its participation keeps growing. This paradox between levels of representation and participation is becoming a meaningful indicator of the ongoing political process in Ecuador, especially in a year of election, where a candidate from a national independent political movement won presidential elections.